2015
DOI: 10.1007/s10661-015-4748-3
|View full text |Cite
|
Sign up to set email alerts
|

Abutilon indicum L.: a prospective weed for phytoremediation

Abstract: This study was aimed to determine the uptake and accumulation potential of a weed (Abutilon indicum L.) for phytoremediation of soil contaminated with cadmium. Plants were grown in soil spiked with 0, 2.5, 5, 10, 15, 20, 25 mg/kg Cd, individually. Plants sample (root and shoot) were analyzed for Cd content at 30, 60, and 90 days and accumulation trends were characterized. A steady increase in Cd accumulation with increasing metal concentration and exposure period was observed for all treatments. Accumulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…The bioaccumulation factor for metals varied as Cd: 619.80 ( C. sativa) − 826.72 ( A. aspera ); Cr: 11.29 ( A. arvensis ) − 35.19 ( S. acuta ); Co: 23.30 ( A.arvensis) − 72.60 ( S. acuta ); Cu: 155.25 ( C. sativa) − 469.16 ( A. arvensis ); Fe: 208.93 ( C. sativa) − 2738.54 ( S. acuta ); Mn: 2.73 ( A. aspera ) − 262.13 ( A. arvensis ); Pb 493.99 (A.arvensis) − 591.34 ( A. conyzoids ); and Zn: 8.09 ( A.aspera) − 592.66 ( A. conyzoids ). Various earlier studies indicated that naturally growing plant/weed species act as promising system for phytoremediation of contaminated areas [ Rehman and Iqbal , ; Pongthornpruek et al , ; Subhashini and Swamy , ; Varun et al , ]. Insight to metal bioaccumulation factor of the plant species provides a scope for decontamination, thereby reducing the pollution load of aquatic as well as terrestrial ecosystems.…”
Section: Resultsmentioning
confidence: 99%
“…The bioaccumulation factor for metals varied as Cd: 619.80 ( C. sativa) − 826.72 ( A. aspera ); Cr: 11.29 ( A. arvensis ) − 35.19 ( S. acuta ); Co: 23.30 ( A.arvensis) − 72.60 ( S. acuta ); Cu: 155.25 ( C. sativa) − 469.16 ( A. arvensis ); Fe: 208.93 ( C. sativa) − 2738.54 ( S. acuta ); Mn: 2.73 ( A. aspera ) − 262.13 ( A. arvensis ); Pb 493.99 (A.arvensis) − 591.34 ( A. conyzoids ); and Zn: 8.09 ( A.aspera) − 592.66 ( A. conyzoids ). Various earlier studies indicated that naturally growing plant/weed species act as promising system for phytoremediation of contaminated areas [ Rehman and Iqbal , ; Pongthornpruek et al , ; Subhashini and Swamy , ; Varun et al , ]. Insight to metal bioaccumulation factor of the plant species provides a scope for decontamination, thereby reducing the pollution load of aquatic as well as terrestrial ecosystems.…”
Section: Resultsmentioning
confidence: 99%
“…The two main mechanisms of the tolerance in the T. africana were its high excretion of the elements through its salt glands and the relatively low translocation of metals from its roots to the other plant parts. Varun et al [ 102 ] reported the weed Abutilon indicum displayed BCF >1 at all concentrations. A. indicum had translocated most of the metals in its root.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, many studies documented the use of weeds as phytoremediators of metals [ 26 , 27 , 28 , 102 , 108 , 109 ]. Generally, the translocations of Cu and Zn from roots to stems and leaves of plants from across the sampling sites were low (TF < 1).…”
Section: Discussionmentioning
confidence: 99%
“…The differential pattern of Cr accumulation in all the species could be adduced to the effect of plant species type. The ability of plant species to accumulate a particular metal is selective and it varies (Alloway et al, 1990;Secu et al, 2008;Lacatusu et al, 2009;Varun et al, 2015). The reported low pH and organic matter of the soil (Fatoba et al, 2016) in the study locations may play a role in enhancing phytoavailability of metals in the soil, resulting in high plant uptake as biomass contents of all metals were higher than the soil contents.…”
Section: Level Of Metal In Tissue Biomass Of the Native Speciesmentioning
confidence: 91%